Heterodyne interferometry for the detection of elastic waves: a tutorial and open-hardware project. (9th March 2015) - Hitchman, Sam; Wijk, Kasper van; Broderick, Neil; Adam, Ludmila
Abstract: Non-contacting acoustic and ultrasonic measurements are of interest in applications ranging from nondestructive evaluation to rock physics and medical imaging. The fundamental workings of the detector—the interferometer—are easily explained in undergraduate physics courses, but practical implementations are dominated by specialized, and commercial, devices. We present a robust and relatively inexpensive detector, which consists of a heterodyne interferometer and phase locked loop frequency demodulator, as an open-source alternative. We illustrate the broadband capabilities with the detection of ultrasonic waves in a mudstone sample, and low-frequency (100 Hz) vibrations of a piston.